2012
DOI: 10.2463/mrms.11.205
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Value of 3D T2*-weighted Imaging with Multi-echo Acquisition: Comparison with Conventional 2D T2*-weighted Imaging and 3D Phase-sensitive MR Imaging

Abstract: Susceptibility-weighted angiography (SWAN) is a state-of-the-art 3-dimensional (3D) T 2 *-weighted imaging (T 2 *WI) technique with multiple echo acquisitions, but its clinical utility remains to be determined. We compared the utility of susceptibility-weighting sequences among SWAN, 3D phase-sensitive magnetic resonance (MR) imaging (PSI), and conventional 2-dimensional (2D) T 2 * WI in routine clinical practice. Our results indicate that SWAN can achieve susceptibility weighting more eŠectively than conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Regarding visualization of brain mineralization, small cerebral veins, and hemosiderin depositions, 1 study demonstrated it to be more valuable than conventional 2-dimensional T2* imaging and as useful as phase-sensitive SWI. 6 Other studies showed the sequence's ability to function as high-resolution magnetic resonance angiography depicting both venous and arterial vessels 5 and the resulting advantages in the imaging of vascular malformations. 8,9 With the additional quality of hypoxia imaging, SWAN should be particularly valuable in the setting of stroke imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding visualization of brain mineralization, small cerebral veins, and hemosiderin depositions, 1 study demonstrated it to be more valuable than conventional 2-dimensional T2* imaging and as useful as phase-sensitive SWI. 6 Other studies showed the sequence's ability to function as high-resolution magnetic resonance angiography depicting both venous and arterial vessels 5 and the resulting advantages in the imaging of vascular malformations. 8,9 With the additional quality of hypoxia imaging, SWAN should be particularly valuable in the setting of stroke imaging.…”
Section: Discussionmentioning
confidence: 99%
“…5 Compared with phasesensitive SWI, SWAN has the advantage of shorter scanning and postprocessing time. 6 We carried out an investigation on the effects on the brain caused by hypoxia as experienced at high altitudes. The subjects were exposed to both short-term and long-term hypoxia to discover possible adaptation mechanisms of the brain to hypoxic conditions.…”
mentioning
confidence: 99%
“…Finally, the multiple echoes captured include echoes with relatively high signal intensity and short TE. These echoes explain the relatively higher SNR for SWAN in comparison to GRE-T 2 * and FSE-T 2 and contributed to a better CNR [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…SWAN features a 1 mm slice thickness in comparison to the 2 mm slice thickness for the other two sequences, making the partial volume effect relevant to characterizing of the anatomic structure. The ability of SWAN to image with slices thinner than those of the other two sequences even though the three sequences have similar imaging times allows a high SNR, with 3D images produced and with multi-echo acquisition [ 16 ]. This ability was also available in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The vessels are visualized without the application of any contrast agent. They have recently been mentioned to be of high clinical value in different neurological diseases, especially in the neurovascular area [10,11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%